2014
DOI: 10.1152/physiolgenomics.00088.2014
|View full text |Cite
|
Sign up to set email alerts
|

Gonadal transcriptomic analysis of yellow catfish (Pelteobagrus fulvidraco): identification of sex-related genes and genetic markers

Abstract: Gonadal transcriptomic analysis of yellow catfish (Pelteobagrus fulvidraco): identification of sex-related genes and genetic markers. Physiol Genomics 46: 798 -807, 2014. First published September 2, 2014; doi:10.1152/physiolgenomics.00088.2014.-Yellow catfish (Pelteobagrus fulvidraco) has been recognized as a vital freshwater aquaculture species in East and Southeast Asia. In addition to its commercial interest, it is also attracted much attention because of its value in studying sex-determination mechanisms.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
25
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 71 publications
9
25
1
Order By: Relevance
“…The GO analysis in this research was similar to the testes transcriptome analysis for the channel catfish by Sun et al, [52] and the yellow catfish by Lu et al, [53]. Four of the top five GO terms in the biological process category for the channel catfish (cellular process, metabolic process, biological regulation, and response to stimulus) and the top four GO terms for the yellow catfish (cellular process, singleorganism process, metabolic process, and biological regulation) matched the top five GO terms in this study [52,53].…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…The GO analysis in this research was similar to the testes transcriptome analysis for the channel catfish by Sun et al, [52] and the yellow catfish by Lu et al, [53]. Four of the top five GO terms in the biological process category for the channel catfish (cellular process, metabolic process, biological regulation, and response to stimulus) and the top four GO terms for the yellow catfish (cellular process, singleorganism process, metabolic process, and biological regulation) matched the top five GO terms in this study [52,53].…”
Section: Discussionsupporting
confidence: 75%
“…The binding, catalytic activity, transporter activity, and molecular transducer GO terms were represented within the top five GO terms of the molecular function category for all three testis transcriptome studies. For the cellular componentcategory, four of the top five GO terms for the channel catfish (cell, organelle, macromolecular complex, and extracellular region) and four of the top five GO terms for the yellow catfish (cell, organelle, membrane, and macromolecular complex) matched the top five GO terms in this study [52,53]. The cell, organelle, and macromolecular complex GO terms were observed within the top five GO terms in all three testis studies.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…These genes have been identified in a few species (Matsuda et al, 2002;Kamiya et al, 2012;Yano et al, 2012) and have been used as chromosomal markers to distinguish pairs of sex chromosomes (Okutsu et al, 2015). In addition, functional genomic studies (transcriptomics) currently applied to fish have identified genes that are complementary to those considered essential for sex determination (Zhang et al, 2011;Yano et al, 2012;Sun et al, 2013;Tao et al, 2013;Lu et al, 2014).…”
Section: Discussionmentioning
confidence: 99%